Dielectric Properties and Characterizations of Binary Cu(2-x)MgxP2O7 Pyrophosphates. Issue 1 (2nd January 2016) - Baitahe, Rattanai; Vittayakorn, Naratip
Abstract : Samples of the binary metal pyrophosphate, Cu(2-x) Mg(x) P2 O7 (x = 0.00 – 2.00), were prepared via solid state reaction. Vibrational bands of [P2 O7 ] 4− anion which contains the O–P–O radical ([PO2 ] − ) and the P–O–P bride ([OPO] − ) and approximate M–O stretching were identified by Raman scattering. A strong P–O–P band was observed clearly in Raman spectra, which indicated the formation of solid solution.The purity of synthetic powders were characterized by X-ray diffraction (XRD).The XRD patterns indicated that all the samples exhibited a single monoclinic phase structure. The complete solid solutions in the Cu(2-x) Mg(x) P2 O7 (x = 0.00 – 2.00) system were obtained. The unit cell volume changed, due to the difference between the final product structure and Cu2 P2 O7 .X-ray absorption near the edge structure (XANES) technique was used to confirm oxidation state of copper in the Cu(2- x ) Mg x P2 O7 .The relative permittivity and dielectric loss of the samples were measured. The bond length and bond angle were analyzed by EXAFS and Raman techniques. The relative permittivity was seen to maintain temperature by substituting Mg 2+ with Cu2 P2 O7 . These results were used to explain the crystal structure of materials in order to change the bond which affects dielectric phenomena.